2011
DOI: 10.1007/s00586-011-1919-y
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide exhibits anti-inflammatory, anti-catabolic as well as anabolic effects and suppresses TLR expression and MAPK activity in IL-1β treated human intervertebral disc cells

Abstract: Introduction Increased levels of proinflammatory cytokines seem to play a pivotal role in the development of back pain in a subpopulation of patients with degenerative intervertebral disc (IVD) disease. As current treatment options are mostly limited to surgical interventions or conservative treatment, anti-inflammatory substances might offer a novel, more target-orientated therapeutic approach. Triptolide (TPL), a natural substance found in the Chinese medicinal herb Tripterygium wilfordii Hook, has been demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…In vivo and in vitro experiments have demonstrated that triptolide has a role in numerous immune disorders, including multiple sclerosis, colitis, lupus nephritis and transplant rejection (6,15,16). The anti-inflammatory activity of triptolide not only activates immune cells, such as T cells and monocytes, Anti-inflammatory effects of triptolide by inhibiting the NF-κB signalling pathway in LPS-induced acute lung injury in a murine model but also resident tissue cells (17,18). In the present study, the anti-inflammatory effects of triptolide were investigated, and the mechanisms underlying the action of triptolide in ALI were explored.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo and in vitro experiments have demonstrated that triptolide has a role in numerous immune disorders, including multiple sclerosis, colitis, lupus nephritis and transplant rejection (6,15,16). The anti-inflammatory activity of triptolide not only activates immune cells, such as T cells and monocytes, Anti-inflammatory effects of triptolide by inhibiting the NF-κB signalling pathway in LPS-induced acute lung injury in a murine model but also resident tissue cells (17,18). In the present study, the anti-inflammatory effects of triptolide were investigated, and the mechanisms underlying the action of triptolide in ALI were explored.…”
Section: Introductionmentioning
confidence: 99%
“…31,39,40 MAPKs are essential molecules involved in innate immune responses to microbes. 39 We demonstrated here that HKBA triggers the phosphorylation of p38 and ERK (Figure 9). However, only the action of p38 controls TLR2-dependent HKBA phagocytosis and phagosome acidification and maturation.…”
mentioning
confidence: 99%
“…In response to infection, plasma and leucocytes are recruited to the affected site to activate other cell types whereas in response to tissue injury a vascular response is also instigated, a process that is more complex in avascular tissue [16]. Cytokines, such as interleukin (IL)-1β, are thought to be mediators in the breakdown of ECM [4,[18][19][20]. Activation of cytokines is believed to proceed through toll-like receptor (TLR)-2 and TLR4 signaling and can lead to increased mRNA expression levels of several inflammatory and catabolic genes including IL-1β, IL-6, IL-8, cyclooxygenase (COX)-2, matrix metalloproteinase (MMP)-1 and -13 [21][22][23].…”
Section: Introductionmentioning
confidence: 99%